2009
DOI: 10.1111/j.1468-1331.2009.02648.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, randomized trial of duloxetine versus placebo in the management of chronic low back pain

Abstract: Duloxetine was superior to placebo on the primary objective from weeks 3-11, but superiority was not maintained at end-point. Duloxetine was superior to placebo on many secondary measures, and was well-tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 34 publications
4
149
1
3
Order By: Relevance
“…Benedetti, 2009) demonstrated that in the chronic pain treatment the patient's expectations concerning the efficacy of the medication significantly improve his or her general condition. During the 13-week observation of the patients suffering from chronic back pain no significant differences in pain severity were observed between the patients who were administered duloxetine and those given placebo (Skljarevski et al, 2009). A number of studies have found that the administration of placebo reduces the severity of pain in a substantial proportion of patients suffering from chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Benedetti, 2009) demonstrated that in the chronic pain treatment the patient's expectations concerning the efficacy of the medication significantly improve his or her general condition. During the 13-week observation of the patients suffering from chronic back pain no significant differences in pain severity were observed between the patients who were administered duloxetine and those given placebo (Skljarevski et al, 2009). A number of studies have found that the administration of placebo reduces the severity of pain in a substantial proportion of patients suffering from chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the efficacy of the serotonin and noradrenaline reuptake inhibitor duloxetine in chronic LBP are conflicting. In a placebo-controlled study (n ¼ 404), the reduction in average weekly pain (measured on a 0-10 Likert scale) was significantly greater with duloxetine at doses of 60 mg than with placebo from weeks 3-11 (p50.05), but this difference was not maintained through to study endpoint (week 13) 93 . Significant improvements in several pain scales were also observed, including the Patient Global Impression of Improvement (PGI-I), Roland Morris Disability Questionnaire (RMDQ-24), Brief Pain Inventory (BPI)-average pain and BPI-average interference.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Active treatment was superior to placebo in both 12-week trials when a 30% improvement in pain was defined as a positive response (Skljarevski et al, 2010a;Skljarevski et al, 2009) but only in 1 trial when a 50% improvement was defined as a positive response (Skljarevski et al, 2010a). Given modest efficacy, duloxetine may be a helpful adjunctive therapy (discussed below).…”
Section: Serotonin-norepinephrine Reuptake Inhibitorsmentioning
confidence: 99%
“…Duloxetine has shown modest efficacy in two 12-week trials (Skljarevski et al, 2010a;Skljarevski et al, 2009) and in a 41-week open-label study (Skljarevski et al, 2010b). Active treatment was superior to placebo in both 12-week trials when a 30% improvement in pain was defined as a positive response (Skljarevski et al, 2010a;Skljarevski et al, 2009) but only in 1 trial when a 50% improvement was defined as a positive response (Skljarevski et al, 2010a).…”
Section: Serotonin-norepinephrine Reuptake Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation